(3VhA GdYbGFO (B( (3Ydi ebOeI HOA GdCeGdj (B)s - (3GdGhTj , Ydj Hf YKeGf Hf SdjeGf Hf eMeO GdJjej GdGhSj (B((3GdGhTj(B) (3GdaQZGfj GdMfaj, SQGL GdOjf CHh eMeO GdGhTj,J (B569 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg hHYO adeG QCjJ LeGYI ef GdCYRGA ai SfI KdGK hSHYeGjI aGdJeShG efi Cf CTQM dgPg GdYbjOI GdeSeGg Hjbhd GdYHO hSejJg VhA GdYbGFO s
(3BNQgG (B:s
(3bGd QMeg Gddg hgPG BNQ eG hLOJ ef cJH GdeTGjN GdSGdaI aLeYJg ai gPG GdTQM OjffG hGYJbGOfG hfSCd Gddg JYGdi Cf jKHJfG Ydjg ZaQ Gddg dg hdhGdOjg hcGJHg s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B700s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds